USE OF BRAZILIANS PLANTS IN HAUTE CUISINE: DISCUSSION OF CONFLITS BETWEEN THE MARKET AND SOCIAL RIGHTS - Catelli, Mariane Ravagio [UNESP]; Risso, Luciene Cristina [UNESP] (Univ Federal Mato Grosso, 2021)
This article is based on the doctoral research of the first author. The research aims to analyze how the relationship between haute cuisine and traditional communities takes place when it comes to the use of Brazilian biodiversity in the elaboration of dishes by these restaurants and to enable the discussion about the conflicts between social rights and the market. With the research, it is expected to expand the discussion on haute cuisine and traditional communities from a geographical perspective, making contributions so that there is a critical reflection and that these relationships can occur in a more equal way among those involved.
Keywords: CULTURAL GEOGRAPHY; GASTRONOMY; TRADITIONAL COMMUNITIES; SOCIAL RIGHTS; SOCIO-ENVIRONMENTAL ANALYSIS